Family capital and entrepreneurial intentions of vocational undergraduates: the chain mediating role of social support and critical thinking - Zhang, Zeqing; Abdullah, Haslinda; Ghazali, Akmar Hayati Ahmad; D’Silva, Jeffrey Lawrence; Ismail, Ismi Arif; Huang, Zerui (Frontiers in Education, 2025)
BackgroundVocational undergraduates in China often face structural barriers in entrepreneurship, including limited family resources, weak social support, and insufficient critical thinking skills. Understanding the psychological mechanisms underlying their entrepreneurial intentions is essential for improving support strategies.ObjectiveThis study investigates the chain mediating effect of social support and critical thinking on the relationship between family capital and entrepreneurial intentions among vocational undergraduate students.MethodsA convenience sampling method was used, with the questionnaire link randomly distributed across departments of a vocational university in Guangdong, China. Data were collected from 858 valid participants through the Wenjuanxing online platform. Four established instruments were used: the Family Capital Scale (FCS), Individual Entrepreneurial Intentions Scale (IEIS), Oslo Social Support Scale (OSSS-3), and the Critical Thinking Disposition Scale (CTDS). Data analysis was conducted using SPSS 27.0 and PROCESS macro with bootstrapping to examine the hypothesized chain mediation model.ResultsFamily capital significantly predicted entrepreneurial intentions (β = 0.523, p < 0.001), social support (β = 0.110, p < 0.001), and critical thinking (β = 0.236, p < 0.001). Social support significantly predicted both critical thinking (β = 0.564, p < 0.001) and entrepreneurial intentions (β = 0.733, p < 0.001). Critical thinking also positively predicted entrepreneurial intentions (β = 0.407, p < 0.001). The total indirect effect of social support and critical thinking was significant, supporting the chain mediation hypothesis.ConclusionFamily capital enhances vocational undergraduates’ entrepreneurial intentions through the mediating roles of social support and critical thinking. The findings highlight the importance of strengthening both external support networks and internal cognitive resources in entrepreneurship education. Policymakers and educators should consider targeted strategies to improve social capital and critical thinking development among vocational students.